Acupuncture and traditional Chinese veterinary medicine for treatment of a mare with rectal paralysis. (10th November 2016) - Sleeper, M. M.; Fishman, K.; MacKay, R. J.; Brown, M.; Bauck, A. G.; Xie, H.
Summary: An 8‐year‐old Appaloosa mare with rectal paralysis due to a cosmetic ethanol 'tail block' was treated with traditional Chinese veterinary medicine treatments including acupuncture and herbal medicine. Her rectal and tail tone gradually improved after the treatment. At 4 months after initial presentation, the mare was able to produce faecal piles on a regular basis, and manual evacuations were no longer needed. Significant improvement was within 30 days of beginning treatment. At 8 months, the owner indicated that the mare had normal defaecation, was able to swish the tail from side to side and lift the tail to urinate, and had no evidence of straining to defaecate or colic.